2022
DOI: 10.1186/s43055-022-00782-4
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT tumor to liver SUV ratio (TLR), tumor SUVmax, and tumor size: can this help in differentiating squamous cell carcinoma from adenocarcinoma of the lung?

Abstract: Background PET/CT plays an essential role in the diagnosis, staging, and follow-up of lung cancer. We aimed to assess the ability of PET/CT to differentiate between adenocarcinomas (AC) and squamous cell carcinomas (SCC) of the lung using tumor size, tumor maximum standardized uptake value (SUVmax), lymph nodes SUVmax, and tumor to liver SUV ratio (TLR). Results A total of 60 patients pathologically proved to have non-small cell lung cancer either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Nevertheless, several studies so far have demonstrated the value of conventional PET radiomics features. For example, Salem et al [28] and Lu et al [29] demonstrated in patients with non-small cell lung cancer undergoing staging PET/CT, the ability of maximal standardized uptake values (SUVmax) to discriminate between AC and SCC. In this regard, some of the representative cases in our study population were provided in Figures 5-7.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several studies so far have demonstrated the value of conventional PET radiomics features. For example, Salem et al [28] and Lu et al [29] demonstrated in patients with non-small cell lung cancer undergoing staging PET/CT, the ability of maximal standardized uptake values (SUVmax) to discriminate between AC and SCC. In this regard, some of the representative cases in our study population were provided in Figures 5-7.…”
Section: Discussionmentioning
confidence: 99%